Developing World Communications - International Inst. of Communications, London (England).; Waller, Andrew; Clarke, Genevieve; International Inst. of Communications, London (England). (Washington : Distributed by ERIC Clearinghouse, 1987)
Designed to provide a means of disseminating expert information on the use of modern communications for development, the goal of this book is to contribute to the equitable sharing of such knowledge globally, and ultimately to the more effective use of the most appropriate equipment available. The book is divided into nine chapters, as follows: (1) Global Telecommunications (focuses on the demand for investment in telecommunications and the advent of satellite communications); (2) Telecommunications Management (presents information on bridging the telecommunications gap, the increasing need for computer based network management systems, and maintaining telecommunications networks); (3) Telecommunications Equipment (acquaints the reader with fiber optic lines, copper cables, intercoms, and other products); (4) Rural Communications (supplies information on developing rural telecommunication networks); (5) Mobile Communications (contains the recent technological achievements in the field); (6) Digitisation and Information Technology (explains recent advances in digital networking and information technology systems); (7) Power (discusses the importance of an uninterruptible power supply); (8) Satellites (examines the progress in satellite communications); and (9) Broadcasting (offers information about several aspects of broadcasting). Advertiser information is presented, including a chart correlating items of equipment with 120 companies. (MS)
Microfiche.
Keywords: Broadcast Reception Equipment; Broadcast Television; Communications Satellites; Developing Nations; Global Approach; Information Technology; International Communication; Modernization; Radio; Technological Advancement; Telecommunications; Broadcast Transmission Equipment; Third World; Collected Works, General; Books